Trend of caesarean deliveries in Egypt and its associated factors: evidence from national surveys, 2005–2014 - Rami H. Al Rifai (BMC Pregnancy and Childbirth, 2017)
Abstract Background The continued rise in caesarean section (c-section) deliveries raises a major public health concern worldwide. This study assessed the trend of c-section deliveries and examined factors associated with a rise in c-section deliveries among the Egyptian mothers, from 2005 to 2014, by place of delivery. Methods This study utilized the 2005, 2008, and 2014 Egypt Demographic and Health Surveys (EDHS). The EDHS reported on the mode of delivery for the last birth occurred within five years preceding each survey including place of delivery and sociodemographic information for a total sample of over 29,000 mothers in the three surveys. To document trend of c-section, the EDHS-2005 was set as a reference in two binary logistic regression models; among all mothers together and for mothers stratified by place of delivery (public or private). P-value for the trend was assessed by entering the year of the survey as a continuous variable. The study followed STROBE statement in reporting observational studies. Results Institutional-based c-sections increased by 40.7 points from EDHS-2005 to EDHS-2014 (aOR, 3.46, 95%CI: 3.15–3.80, P trend  < 0.001). Compared to mothers with low socioeconomic status (SES), mothers with high SES had higher odds (aOR, 1.78, 95%CI: 1.25–2.54, P = 0.001) for c-section, but only in EDHS-2005. The adjusted trend of c-sections was found to be 4.19-time (95%CI: 3.73–4.70, P < 0.001) higher in private sector while that in public sector it was 2.67-time (95%CI: 2.27–3.13, P = 0.001) higher, in EDHS-2014 relative to EDHS-2005. This increase in the private sector is explained by significant increases among mothers who are potentially at low risk for c-sections; mothers aged 19-24 years vs. ≥35 years (aOR: 0.31, 95%CI: 0.21–0.45, in EDHS-2005 vs. 0.43, 95%CI: 0.33–0.56, in EDHS-2014, P < 0.001); primigravida mothers vs. mothers with ≥4 children (aOR: 1.62, 95%CI: 1.12–2.34, in EDHS-2005 vs. 3.76, 95%CI: 2.94–4.80 in EDHS-2014); and among normal compared to high risk birth weight babies (aOR: 0.79, 95%CI: 0.62–0.99 in EDHS-2005 P < 0.05 vs. 0.83, 95%CI: 0.65–1.04 in EDHS-2014, P > 0.05). Conclusions Results showed a steady rise in c-sections in Egypt that has reached an alarming level in recent years. This increase appears to be associated with a shift towards delivery in private health care facilities. More vigilance of c-section deliveries, particularly in the private sector, is warranted.